Prehospital Pediatric Respiratory Distress and Airway Management Interventions: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Harris, Matthew; Lyng, John W.; Mandt, Maria; Moore, Brian; Gross, Toni; Gausche-Hill, Marianne; Donofrio-Odmann, J. Joelle
Abstract: Devices and techniques such as bag-valve-mask ventilation, endotracheal intubation, supraglottic airway devices, and noninvasive ventilation offer important tools for airway management in critically ill EMS patients. Over the past decade the tools, technology, and strategies used to assess and manage pediatric respiratory and airway emergencies have evolved, and evidence regarding their use continues to grow. NAEMSP recommends: Methods and tools used to properly size pediatric equipment for ages ranging from newborns to adolescents should be available to all EMS clinicians. All pediatric equipment should be routinely checked and clearly identifiable in EMS equipment supply bags and vehicles. EMS agencies should train and equip their clinicians with age-appropriate pulse oximetry and capnography equipment to aid in the assessment and management of pediatric respiratory distress and airway emergencies. EMS agencies should emphasize noninvasive positive pressure ventilation and effective bag-valve-mask ventilation strategies in children. Supraglottic airways can be used as primary or secondary airway management interventions for pediatric respiratory failure and cardiac arrest in the EMS setting. Pediatric endotracheal intubation has unclear benefit in the EMS setting. Advanced approaches to pediatric ETI including drug-assisted airway management, apneic oxygenation, and use of direct and video laryngoscopy require further research to more clearly define their risks and benefits prior to widespread implementation. If considering the use of pediatric endotracheal intubation, the EMS medical director must ensure the program provides pediatric-specific initial training and ongoing competency and quality management activities to ensure that EMS clinicians attain and maintain mastery of the intervention. Paramedic use of direct laryngoscopy paired with Magill forceps to facilitate foreign body removal in the pediatric patient should be maintained even when pediatric endotracheal intubation is not approved as a local clinical intervention.